2017
DOI: 10.1021/acs.biochem.6b01252
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Investigations on Histone H2A-H2B Dynamics in the Nucleosome

Abstract: Nucleosomes impose physical barriers to DNA-templated processes, playing important roles in eukaryotic gene regulation. DNA is packaged into nucleosomes by histone proteins mainly through strong electrostatic interactions that can be modulated by various post-translational histone modifications. Investigating the dynamics of histone dissociation from the nucleosome and how it is altered upon histone modifications is important for understanding eukaryotic gene regulation mechanisms. In particular, histone H2A-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 50 publications
(108 reference statements)
5
32
0
Order By: Relevance
“…Single-molecule fluorescence measurements are widely utilized to investigate protein dynamics including the detection of conformational changes, stoichiometry, and protein mobility (17,19,20). Experiments with this level of detail are only feasible after purification of the protein from its physiological cellular environment (21,22). This type of purification is not achievable for many types of membrane proteins, which lose their structural and functional integrity when removed from their native cellular environment.…”
mentioning
confidence: 99%
“…Single-molecule fluorescence measurements are widely utilized to investigate protein dynamics including the detection of conformational changes, stoichiometry, and protein mobility (17,19,20). Experiments with this level of detail are only feasible after purification of the protein from its physiological cellular environment (21,22). This type of purification is not achievable for many types of membrane proteins, which lose their structural and functional integrity when removed from their native cellular environment.…”
mentioning
confidence: 99%
“…Between pauses, gradually changing fluorescence intensities are observed, suggesting that the DNA is unwrapping as the elongation complex translocates. Gradual dissociation of H2A-H2B with no change in DNA is another possibility, which is extremely unlikely considering the structure of the nucleosome and according to our published data even at an elevated salt concentration [49]. If it is still desired to rule out this possibility, a control experiment can be carried out with a FRET pair labeled at both gyres of DNA near the dimer-DNA contact region.…”
Section: Data Interpretationmentioning
confidence: 97%
“…Single-molecule methods provide a powerful means to interrogate such a complex process in real-time in a timeresolved manner. This review is to focus on our single-molecule experimental systems and methods that we reported to investigate nucleosome dynamics [44][45][46][47][48][49][50][51][52][53][54][55][56][57]. In particular, we recently reported an experimental system and method with which we can investigate the real-time dynamics of RNAPII translocation along nucleosomal DNA [56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, two global pathways for nucleosome disassembly may be envisaged, either dissociation of the octamer as a single entity from the DNA or sequential release of histones or groups of histones; the second hypothesis is now generally accepted. A series of studies of salt-induced dissociation based on FRET (Forster Resonance Energy Transfer) approaches [1], 2, 11, 12, [11-14] [2) or TR-SAXS (Time-Resolved Small Angle X-ray Scattering) {Chen, 2014 #3253, 15,16] [17] provided coherent arguments in favour of a pathway with two major successive phases: a first step leading to the release of H2A-H2B dimers and a second, distinct step corresponding to (H3-H4)2-DNA dissociation.…”
Section: Introductionmentioning
confidence: 99%